Skip to main content

Coordinated Differential Equations

Section 2.4 Forcing and Resonance

Resonance happens when the natural frequency and the forcing frequency of an undamped harmonic oscillator are the same. There are many real world examples of resonance. For example, it is possible for a trained singer to shatter a champagne glass by simply singing the correct note (see www.youtube.com/watch?v=IZD8ffPwXRo). Shattering a glass by singing the correct note can be modeled by an equation of an undamped harmonic oscillator with sinusoidal forcing. While a certain amount of damping occurs in all physical systems, the damping is often so small that it makes sense to use an undamped harmonic oscillator.

Subsection 2.4.1 Resonance

Resonance was responsible for the collapse of the Broughton suspension bridge near Manchester, England in 1831. The collapse occurred when a column of soldiers marched in cadence over the bridge, setting up a periodic force of rather large amplitude. The frequency of the force was approximately equal to the natural frequency of the bridge. Thus, the bridge collapsed when large oscillations occurred. For this reason soldiers are ordered to break cadence whenever they cross a bridge.
The Millennium Bridge, the first new bridge to span the Thames River in London in over 100 years, is a modern example of how resonance can effect a bridge (Figure 2.4.1). This pedestrian bridge, which opened to the public in June 2000, was quickly closed after the bridge experienced high amplitude horizontal oscillations during periods of high traffic. Studies by designers found that the bridge experienced high amplitude horizontal oscillations in response to horizontal forcing at a rate of one cycle per second. Typically, people walk at a rate of two steps per second, so the time between two successive steps of the left foot is about one second. Thus, if people were to walk in cadence, they could set up strong horizontal forcing that would place a destructive load on the bridge. The engineers did not envision this to be a problem since tourists do not generally march in time. However, a video of tourists crossing the bridge revealed the opposite. When the bridge began oscillating, people tended to walk in cadence in order to keep their balance (www.youtube.com/watch?v=gQK21572oSU).
described in detail following the image
a photo of the Millennium Bridge in London
Figure 2.4.1. The Millennium Bridge
Consider the case of an undamped harmonic oscillator with a sinusoidal forcing function. We know that we can model this situation with the second-order linear differential equation
x+ω02x=Acosωt.
Since the homogeneous solution to this equation is
xh(t)=c1cosω0t+c2sinω0t,
we can see that the natural frequency of the harmonic oscillator is ω0. This is the frequency of the oscillations if there is no forcing term. Depending on whether or not the frequency of the forcing term ω is equal to the natural frequency, we will have two very different situations. If the two frequencies are equal, then they will re-enforce one another and we will have resonance. If the two frequencies are close but not equal, we will see the phenomenon of beats. We wish to investigate what happens when the driving frequency ω is equal to the natural frequency and when it is not.
Let us examine the case where the forcing frequency and the natural frequency of the oscillator are the same,
(2.4.1)x+ω02x=Acosω0t.
Since Acosω0t is a solution to the homogeneous equation x+ω02x=0, we cannot assume that a particular solution to equation (2.4.1) has the form acosω0t+bsinω0t. Equivalently, if we use the complex method, we cannot assume that our solution has the form aeiω0t. Therefore, we will look for a complex solution of the form
xc=ateiω0t
for the complex equation that corresponds to (2.4.1),
(2.4.2)x+ω02x=Aeiω0t.
In this case,
xc=a(1+iω0t)eiω0txc=a(2iω0ω02t)eiω0t.
Substituting xc and xc into the left-hand side of (2.4.2), we have
xc+ω02xc=a(2iω0ω02t)eiω0t+ω02ateiω0t=2aiω0eiωt.
In order for xc=ateiω0t to be a solution to (2.4.2), we must have
a=A2iω0.
Thus, our solution to the complex form of the differential equation is
xc=A2iω0teiω0t=Ai2ω0teiω0t=Ai2ω0t(cosω0t+isinω0t)=A2ω0tsinω0tiA2ω0tcosω0t.
The real part of xc,
xp(t)=A2ω0tsinω0t,
is a particular solution to (2.4.1). Thus, our general solution is
x(t)=xh(t)+xp(t)=c1cosω0t+c2sinω0t+A2ω0tsinω0t.

Example 2.4.2.

Now let us consider the initial value problem
x+144x=4cos12tx(0)=0x(0)=0.
where A=4 and ω0=12. The solution to the homogeneous equation x+144x=0 is
xh(t)=c1cos12t+c2sin12t.
To find a particular solution to x+144x=4cos12t, we will use the complex method and try to find a particular solution to x+144x=4e12it. We must assume that the solution has the form xc(t)=ate12it, since ae12it is a solution to the homogeneous equation. As before, we have xc=a(24i144t)e12it. If we substitute xc and xc into the left-hand side of our differential equation, we have
xc+144xc=a(24i144t)e12it+144ate12it=24aie12it.
Therefore,
a=424i=16i,
and our complex solution is
16ite12it=16it(cos12t+isin12t)=16tsin12t16itcos12t.
Taking the real part of our complex solution, we have a particular solution
xp(t)=16tsin12t.
Thus, the general solution to x+144x=4cos12t is
x(t)=xh(t)+xp(t)=c1cos12t+c2sin12t+16tsin12t.
Applying the initial conditions, both c1=0 and c2=0. Consequently, the solution to the initial value problem is
x(t)=16tsin12t.
The graph of this solution is given in Figure 2.4.3. Notice that our solution grows with time. This growth is due to the fact that the frequency of the forcing term is equal to the natural frequency of the oscillator. Since the force pulls and pushes at a frequency equal to the natural frequency of the oscillator, the amplitude increases with time. This type of behavior is called resonance.
described in detail following the image
an oscillating position curve with amplitudes increasing as time increases
Figure 2.4.3. The solution to x+4x=4sin2t, x(0)=0, x(0)=0 .

Activity 2.4.1. Resonance.

Solve each of the following initial value problems and plot the solution for t0. In each case, what is the natural (and forcing) frequency of the harmonic oscillator?
(a)
x+121x=3cos11tx(0)=0x(0)=0.
(b)
x+169x=5cos13tx(0)=0x(0)=0.

Subsection 2.4.2 Beats or the Case ωω0

If the forcing frequency and natural frequency are not equal but close, then we have the phenomenon of beats. For example, a piano tuner uses this phenomenon to make certain that a particular string is correctly tuned. The tuner will strike a tuning fork which vibrates at the correct frequency. Next, the tuner hits the poorly tuned piano string. This modulation gives rise to beats in the tone that are readily audible. When the string is properly tuned, the beats will go away. To see another example of beats, watch the video www.youtube.com/watch?v=pRpN9uLiouI.
To understand the situation where the forcing and natural frequencies differ by a small amount, ωω0, we will first consider the equation,
(2.4.3)x+ω02x=Acosωt.
The solution to the homogeneous equation x+ω02x=0 is
xh(t)=c1cosω0t+c2sinω0t.
Since the forcing frequency is not equal to the natural frequency, we can look for a particular solution to the complex of the form of equation (2.4.3),
(2.4.4)x+ω02=Aeiωt.
If we assume that our solution has the form xc=aeiωt and substitute xc into the left-hand side of (2.4.4), we find
xc+ω02xc=aω2eiωt+ω02aeiωt=a(ω02ω2)eiωt.
Therefore, for xc=aeiωt to be a solution for
x+ω02x=Aeiωt,
we must have
a=Aω02ω2.
The real part of xc is a particular solution to (2.4.3),
xp(t)=Aω02ω2cosωt.
Thus, the general solution to (2.4.3) is
x(t)=xh(t)+xp(t)=c1cosω0t+c2sinω0t+Aω02ω2cosωt.
Now let us examine the case where the motion starts at equilibrium. That is, we will investigate what happens when x(0)=0 and x(0)=0. In this case, we can easily determine that c1=A/(ω02ω2) and c2=0. Hence the solution to our initial value problem is
(2.4.5)x(t)=Aω02ω2(cosωtcosω0t).
Thus, we have a superposition to two oscillations of different frequencies.
To understand how the superposition of the two frequencies works, we will let
ω=ω0+ω2
be the mean frequency and
δ=ω0ω2
be the half difference. Since ω=ωδ and ω0=ω+δ, we know that
x(t)=Aω02ω2(cosωtcosω0t)=A(ω+δ)2(ωδ)2(cos[(ωδ)t]cos[(ω+δ)t])=A4ωδ[cos(ωtδt)cos(ωt+δt)]=A4ωδ[cos(ωt)cos(δt)+sin(ωt)sin(δt)cos(ωt)cos(δt)+sin(ωt)sin(δt)]=A4ωδ[2sin(ωt)sin(δt)]=Asinδt2ωδsinωt.
Thus, we have a sine function, sinωt whose amplitude varies according to |(A/2ωδ)sinδt|, and
(2.4.6)x(t)=Asinδt2ωδsinωt.

Example 2.4.4.

In the initial value problem
(2.4.7)x+144x=4cos(13t)(2.4.8)x(0)=0(2.4.9)x(0)=0,
we have A=4, ω0=12, and ω=13. The solution to this equation is
x(t)=425(cos12tcos13t).
The graph of this solution is given in Figure 2.4.5 and illustrate the phenomenon of beats. The two frequencies are almost equal and interfere with each other.
described in detail following the image
an oscillating solution curve with the amplitudes also oscillating
Figure 2.4.5. Solution to the initial value problem (2.4.7)
In our example, δ=1/2 and ω=25/2. The factor sinδt=sin(t/2) in (2.4.6) oscillates very slowly in comparison to sin(ω)=sin(25t/2). Thus, we can view the solution (2.4.6) as a fast oscillation with a frequency ω and amplitude
(2.4.10)|Asinδt2ωδ|=|825sin(t2)|,
which oscillates much more slowly. If we superimpose the graph of (2.4.10) onto the graph in Figure 2.4.5, we obtain an envelope of the faster oscillation.
described in detail following the image
an oscillating solution curve with the amplitudes also oscillating and an envelope curve that bounds the oscillating amplitudes
Figure 2.4.6. Envelope for the initial value problem (2.4.7)

Activity 2.4.2. Beats.

Consider the initial value problem
x+196x=4cos(15t)x(0)=0x(0)=0.
(a)
Solve the initial value problem and plot its solution.
(b)
Calculate the mean frequency, ω=(ω0+ω)/2, and the half difference, δ=(ω0ω)/2, where ω0 is the natural frequency and ω is the forcing frequency and rewrite the solution to the initial value problem in the form (2.4.6).
(c)
Plot the envelope, |(Asinδt)/(2ωδ)|, over the plot of the solution to the initial value problem.
(d)
Discuss what is going on in this activity.

Subsection 2.4.3 Forced Damped Harmonic Motion

Since perpetual motion does not really exist, we should consider what happens when we add some damping to our harmonic oscillator,
(2.4.11)x+2cx+ω02x=Acosωt.

Example 2.4.7.

Let us consider the differential equation
(2.4.12)x+2x+2x=3cos4t.
The corresponding homogeneous equation is
x+2x+2x=0,
which has solution
xh(t)=c1etcost+c2etsint.
To find a particular solution for the equation (2.4.12), we will look for a solution of the form xc=ae4it to the equation
(2.4.13)x+2x+2x=3e4it
and then set xp(t) to the real part of the solution. Substituting xc into the lefthand side of (2.4.13), we obtain
xc+2xc+2xc=(14+8i)ae4it=P(4i)ae4it=3e4it,
where P(λ)=λ2+2λ+2 is the characteristic polynomial of x+2x+2x=0. Therefore,
a=3P(4i)=314+8i=3130(7+4i),
and the solution to the complex equation is
xc=3130(7+4i)e4it=3130(7+4i)(cos4t+isin4t)=3130[(7cos4t+4sin4t)+i(4cos4t7sin4t)].
Thus, we can determine a particular solution by taking the real part of xc,
xp(t)=3130(7cos4t+4sin4t).
The general solution for (2.4.12) is
x(t)=xh(t)+xp(t)=c1etcost+c2etsint+3130(7cos4t+4sin4t).
It is easy to see that all solutions approach xp(t) as t no matter what the initial conditions may be. However, it would be much more useful if we would write the particular solution in the form
xp(t)=Kcos(4tϕ)
for some constants K and ϕ rather than a linear combination of cos4t and sin4t.
Returning to the general case, the associated homogeneous equation for (2.4.11) is
(2.4.14)x+2cx+ω02x=0.
The characteristic polynomial of (2.4.14),
(2.4.15)P(λ)=λ2+2cλ+ω02,
has roots
λ=c±c2ω02.
If our harmonic oscillator is undedamped (c<ω0), then the solution to the homogeneous equation (2.4.14) is
xh=ect(c1cosβt+c2sinβt),
where β=ω02c2.
As in Example 2.4.7, we will look for a particular solution to (2.4.11) by examining the equivalent complex differential equation. That is, we shall look for a solution of the form xc=aeiωt to the equation
(2.4.16)xc+2cxc+ω02xc=Aeiωt,
and then set xp equal to the real part of our solution. Substituting xc into the right-hand side of (2.4.16), we obtain
xc+2cxc+ω02xc=[(iω)2+2c(iω)+ω02]aeiωt=P(iω)aeiωt,
where P is the characteristic polynomial (2.4.15). Thus, equation (2.4.16) becomes
P(iω)aeiωt=Aeiωt,
and
xc(t)=aeiωt=AP(iω)eiωt=H(iω)Aeiωt,
where
H(iω)=1P(iω).
We say that H(λ)=1/P(λ) is the transfer function.
Let us examine the transfer function more closely to see if we can use it to write our particular solution in a more useable form. First, let us write
P(iω)=(iω)2+2c(iω)+ω02=(ω02ω2)+2icω.
in polar form,
P(iω)=Reiϕ=R(cosϕ+isinϕ),
where
R=(ω02ω2)2+4c2ω2
and ϕ is the angle defined by the equations
cosϕ=ω02ω2(ω02ω2)24c2ω2,sinϕ=2cω(ω02ω2)24c2ω2.
Since 2cω>0, we know that sinϕ>0. Equivalently, 0<ϕ<π. Thus,
ϕ=ϕ(ω)=cot1(ω02ω22cω).
Therefore, we can write the transfer function as
H(iω)=1P(iω)=1Reiϕ.
We define the gain to be
G(ω)=1R=1(ω02ω2)2+4c2ω2,
and we will rewrite the transfer function as
H(iω)=G(ω)eiϕ(ω).
Thus, the solution to
xc+2cxc+ω02xc=Aeiωt
(2.4.17)xc(t)=H(iω)Aeiωt=G(ω)Aei(ωtϕ).
Taking the real part of (2.4.17), our particular solution is
xp(t)=Re(xc(t))=G(ω)Acos(ωtϕ).
It is now clear that particular solution has the same frequency as the forcing term. In addition, xp is out of phase with the driving force by the amount
ϕ=ϕ(ω)=cot1(ω02ω22cω).
The general solution to
x+2cx+ω02x=Acosωt
x(t)=xh(t)+xp(t)=ect(c1cos(ηt)+c2sin(ηt))+G(ω)Acos(ωtϕ).
Since xh has the factor ect, the homogeneous part of the solution quickly decays to zero as t. For this reason, xh is called the transient term while xp is called the steady-state term.

Example 2.4.8.

Let us examine the steady-state solution of the harmonic oscillator in Example 2.4.7. We have already determined that the second-order linear differential equation
x+2x+2x=3cos4t
has solution
x(t)=xh(t)+xp(t)=c1etcost+c2etsint+3130(7cos4t+4sin4t).
The natural frequency is ω0=21.4142 If we choose the initial conditions so that c1=0 and c2=1, our transient term is
xh(t)=ectsinβt=etsint.
Since c=1, ω=4, and A=3, the gain is G(4)0.0620, the amplitude of the steady state solution is G(4)40.2481. The phase is ϕ=ϕ(4)2.6224. The solution and the steady-state solution are given in Figure 2.4.9. As we can see, transient solutions can be quite large when compared to steady-state solutions.
described in detail following the image
an oscillating steady-state solution and a solution curve to a forced damped harmonic oscillator that converges to the steady-state solution
Figure 2.4.9. A forced damped harmonic oscillator and the steady-state solution.
Large transient currents can be destructive in electrical circuits. For example, a light bulb usually burns out when a large transient flows through an already weakened bulb. This, usually occurs at the time the light bulb is turned out or turned off. Large transient currents are particularly harmful to the hard drive in a computer. For this reason, computers should be left on except in the case that they are not being used for a period of several days.

Subsection 2.4.4 Important Lessons

  • A forced damped harmonic oscillator,
    x+2cx+ω02x=Acosωt
    has homogeneous solution
    xh=ect(c1cosηt+c2sinηt),
    where η=ω02c2. A particular solution is given by
    xp(t)=Re(xc(t))=G(ω)Acos(ωtϕ),
    where the phase angle ϕ is
    ϕ=ϕ(ω)=cot1(ω02ω22cω)
    and the gain G is given by
    G(ω)=1(ω02ω2)2+4c2ω2.
  • The amplitude and phase of the steady-state solution,
    xp(t)=G(ω)Acos(ωtϕ),
    are determined by
    ω02G=1(1s2)2+D2s2,
    where ω=sω0 and D=2c/ω0.
  • In an undamped harmonic oscillators with a sinusoidal forcing term, the natural frequency of the solution interacts with the frequency of the forcing term. As the frequency of the forcing term approaches the natural frequency of the equation, we can observe a phenomenon called resonance. We can use the equation
    x+ω02x=Acosωt
    to model an undamped harmonic oscillator with sinusoidal forcing.
  • If the driving frequency is not equal to the natural frequency (ωω0), we have a particular solution
    xp(t)=Aω02ω2(cosωtcosω0t).
    If the two frequencies are close, we can see a phenomenon called beats .
  • If the driving frequency is equal to the natural frequency, we have a particular solution
    xp(t)=A2ω0tsinω0t.
    In this case, we can see the resonance phenomenon.
  • A forced damped harmonic oscillator,
    x+2cx+ω02x=Acosωt
    has homogeneous solution
    xh=ect(c1cosηt+c2sinηt),
    where η=ω02c2. A particular solution is given by
    xp(t)=Re(xc(t))=G(ω)Acos(ωtϕ),
    where the phase angle ϕ is
    ϕ=ϕ(ω)=cot1(ω02ω22cω)
    and the gain G is given by
    G(ω)=1(ω02ω2)2+4c2ω2.

Reading Questions 2.4.5 Reading Questions

1.

Describe what resonance means in your own words.

2.

Describe in words alone what the steady state solution of a damped harmonic oscillator is.

Exercises 2.4.6 Exercises

Beats and Resonance.

Solve the initial problems in Exercise Group 2.4.6.1–6. Do you find any beats or resonance?
1.
y+y=cost, y(0)=0, y(0)=0
2.
y+y=cos(11t/10), y(0)=0, y(0)=0
3.
y+4y=sin2t, y(0)=1, y(0)=0
4.
y+4y=3sin(13t/12), y(0)=1, y(0)=1
5.
y+16y=5cos4t, y(0)=1, y(0)=0
6.
y+16y=5cos(4t+1), y(0)=0, y(0)=0

Plotting the Envelope for Beats.

For each of the functions in Exercise Group 2.4.6.7–10 compute the envelope function. Then plot y(t) and the envelope function on the same set of axes.

11.

Consider the function y=cos10tcos11t.
  1. Find the mean frequency ω=(ω0+ω)/2 and half difference δ=(ω0ω)/2.
  2. Use (a) to show that
    y=cos10tcos11t=2sin(12t)sin((212t).
    You will find the following trigonmetric identity very useful,
    2sinAsinB=cos(AB)cos(A+B).
  3. Using (b), plot the graph of y and 2sin(t/2) on the same axes.

12.

For large t, every solution of
y+py+qy=cosωt
oscillates with angular frequency ω and amplitude A given by
A(ω,p,q)=1(qω2)2+p2ω2.
That is, the amplitude of A is a function of the parameters ω , p, and q.
  1. Compute Aω.
  2. For fixed p and q, let M(p,q) denote the maximum value of A(ω,p,q) as a function of ω. Compute an expression for M(p,q).
  3. Set q=1 and plot M(p,q) as a function of p.
  4. Explain why M(p,q) is proportional to 1/p as p0 .

13.

Let us examine the amplitude and phase of the steady-state solution,
xp(t)=G(ω)Acos(ωtϕ),
where
G(ω)=1(ω02ω2)2+4c2ω2.
Now let s=ω/ω0 and D=2c/ω0. These new constants, s and D, measure the ratio of the driving frequency to the natural frequency and the effect of the damping force, respectively. Thus,
G=1ω02(1s2)2+D2s2
ω02G=1(1s2)2+D2s2.
This expression shows us how the gain varies as s=ω/ω0 varies. The natural frequency is fixed in
x+2cx+ω02x=Acosωt
and D=2c/ω0 is proportional to the damping constant.